Dynamics of HBsAg clearance in a UK cohort of chronic HBV infection - Downs, L; Patel, M; Ansari, M; McNaughton, A; Smith, D; Andersson, M; Barnes, E; Jeffery, K; Matthews, P (Elsevier, 2018)
Hepatitis B surface antigen (HBsAg) has recently gained traction as a biomarker that may provide prognostic information and inform treatment decisions in chronic hepatitis B virus (HBV) infection. It may be particularly useful when HBV DNA levels are low and therefore difficult to quantify accurately, either as a result of treatment or natural immune control of the virus. There are few published descriptions of the kinetics of HBV clearance, and most existing data come from Asia. We therefore set out to identify adults who cleared HBsAg in a UK cohort, to characterise those who clear, and to describe the dynamics of HBsAg clearance.